FRI0188 Diastolic dysfunction in patients with scleroderma: a tissue doppler study. (1st June 2001) - Dinc, A; Uzun, M; Pay, S; Simsek, I; Kilicarslan, F; Erdem, H
Abstract : Background: Systemic sclerosis may involve myocardium and brings about myocardial fibrosis. Objectives: In our study, left ventricular diastolic functions were evaluated with the tissue Doppler echocardiography, a newer and more sensitive method than others. Methods: Standard and tissue Doppler echocardiography were applied to 11 patients with systemic sclerosis. Systolic and valve functions were evaluated with standard echocardiography and then the signals obtained from the lateral section of mitral annulus were analysed with pulse wave tissue Doppler echocardiography. Left ventricular diastolic functions were assessed by calculating early wave (E), atrial wave (A) and E/A ratio of these signals. Results: The impairment of left ventricular diastolic functions was determined in 4 patients. This finding was not related to the duration of disease and the spread of involvement. All patients have normal ejection fractions. Conclusion: Left ventricular diastolic dysfunction is a newly defined special feature for cardiac involvement of systemic sclerosis. This finding may be due to myocardial ischemia, fibrosis, or both of them. However, larger studies are necessary to evaluate the prognostic importance of this finding.